Can Brand Image, Price Perception, and Product Quality Improve Purchase Decisions? A Study of Students’ Perceptions - Maura Adriandini Bialista; Ayu Nurafni Octavia (Universal Business and Management Review, 2025)
The rapid development of technology has made people need smartphones to carry out all their activities. Xiaomi is one of the 4th largest smartphone manufacturers in the world, but have not been successful and have not been able to maintain competition in terms of recognizing consumer needs and desires compared to similar companies. This study aims to determine the effect of brand image, price perception, and product quality on purchasing decisions for Xiaomi smartphones at the Faculty of Economics, Semarang University. The method used for data collection is a questionnaire with a Likert scale, with a total of 96 respondents. The type used a quantitative descriptive study. The sampling technique employs a non-probability sampling approach, specifically a purposive sampling method., The data analyzed using SPSS 26. The data analysis test used validity tests, reliability tests, multiple linear regression analysis, hypothesis testing through t-tests, F-tests, and coefficients of determination. The results show that the brand image variable does not have a significant effect on purchasing decisions. Furthermore, the price perception variable has a positive and significant effect on purchasing decisions. The study concludes that the product quality variable has a positive and significant effect on purchasing decisions.